2020
DOI: 10.1108/cc-10-2019-0036
|View full text |Cite
|
Sign up to set email alerts
|

Is grey literature really grey or a hidden glory to showcase the sleeping beauty

Abstract: Purpose The study aims to showcase the developmental perspective of “grey literature” and its importance to different sectors of the society. Furthermore, issues, challenges and possibilities concerned with the existence of “grey literature” have also been discoursed. Design/methodology/approach The study is based on the existing literature published in the field of “grey literature” which was identified with the aid of three leading indexing and abstracting services, Web of Science, SciVerse Scopus, and Goo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 74 publications
0
10
0
1
Order By: Relevance
“…In our investigation, our findings show that beyond the GL evidence supported some findings of TL sources, its use contributed with exclusive evidence that would not exist if GL were not investigated. It shows the importance of GL to address topics that are missing from TL sources [7].…”
Section: Revisiting Findingsmentioning
confidence: 98%
“…In our investigation, our findings show that beyond the GL evidence supported some findings of TL sources, its use contributed with exclusive evidence that would not exist if GL were not investigated. It shows the importance of GL to address topics that are missing from TL sources [7].…”
Section: Revisiting Findingsmentioning
confidence: 98%
“…Its strongest contribution may be in the conduct of scoping reviews, where it is a recommended source to search along with scientific bibliographic databases. The aim of a scoping review is to provide an overview of a field of research, quite often with a focus on providing a general picture on the available literature for a topic [ 22 , 23 ] or understanding the context for an intervention [ 9 ]. Gray literature suits both these purposes well.…”
Section: Introductionmentioning
confidence: 99%
“…Gray literature in many cases lacks time-saving functionality—for example, when exporting references to references management tools. It is also often less structured (eg, lacking abstracts), which makes any screening process less efficient [ 8 , 23 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diversity of scientific areas, e.g., in medicine [25], in management [2], and nutrition [1], have investigated the GL. Some researchers observed that benefits of using GL included gaining significant knowledge from practitioners in addition to academic articles [2], reducing publication bias where studies only report the positive findings to be published [25], and in a way to address topics that are missing from conventional academic sources [14].…”
Section: Introductionmentioning
confidence: 99%